LIVER FUNCTION TESTS IN PATIENTS OF PULMONARY TUBERCULOSIS USING FOUR DIFFERENT DRUG REGIMENS - AKBRI, M ZAMIR AHMAD; FATIMA, NIGHAT; HAQUE, EHSAN UL; SHEIKH, ABDUS SALAM; BHATTI, MUHAMMAD SARWAR (Journal of Ayub Medical College Abbottabad, 2001)
Background: Chemotherapy is the basic approach to clinical tuberculosis control. Antituberculous therapy causes derangement of hepatic functions revealed by disturbed liver function tests. The incidence of side effects may vary depending upon a number of factors. The primary purpose of this study was to determine the relative and absolute hepatotoxicity of different antituberculous drug regimens in Pakistani population where majority of the tuberculous patients belong to poor socioeconomic status. Methods: One hundred patients between 30 to 70 years of age with newly diagnosed pulmonary tuberculosis were selected and divided into four groups on the basis of different drug regimens. Blood and urine tests of these patients were made. Liver function tests were performed before therapy and then after one. two. three, six and nine months of treatment. Results <& Conclusions: Antituberculous therapy causes derangement of hepatic function to a variable extent in patients of four different antituberculous drug regimens under study. Drug combination of Streptomycin. Isoniazid and Myambutol seem to be best tolerated of all the four regimens. Monitoring of the liver function in patients on antituberculous therapy indicated that liver dysfunction most frequently occurs during first three months of therapy. There is a tendency for enzyme values to return to normal inspite of continuous treatment. The mechanism underlying this adaptation to injury to the liver is unknown. Biochemical tests in the patients presenting with jaundice yielded the pattern of acute hepatocellular necrosis with high transaminases and moderately elevated Alkaline Phosphatase. None of the patients had hepatitis associated antigen in their serum.